Detection and Identification of Pathogenic Bacteria in Monomorium sp. Ant in The Environment of Kendari City Hospital, Southeast Sulawesi - Amirullah, Amirullah; Yanti, Nur Arfa; Surachma, Wahyuni Nurul; Suriana, Suriana (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Monomorium sp. ant is one of the insects that are considered pests in the hospital environment and potential to be mechanical vectors that can carry and spread pathogenic bacteria and cause nosocomial infections. This study aims to detect and identify pathogenic bacteria found in Monomorium sp. ants originating from the environment of Kendari City Hospital, Southeast Sulawesi. Sampling of Monomorium sp. was carried out by the bait/sugar trap method in 3 locations of Kendari City Hospital, namely internal inpatient rooms, nutrition installations, and laboratory installations. Detection of pathogenic bacteria was carried out by the pour plate method on selective media, namely MacConkey Agar and Mannitol Salt Agar. The identification of bacteria was carried out by numerical-phenetic analysis based on phenotypic characters using the MVSP 3.1 application. The results of the study identified 5 species of pathogenic bacteria found in Monomorium sp. ants from the Kendari City Hospital environment. Three species of bacteria were found in ants from the internal inpatient room, namely Pseudomonas aeruginosa, Stenotrophomonas maltophilia, and Brevundimonas vesicularis, and two species found in ants from nutrition installations, namely Pseudomonas luteola and Staphylococcus auricularis. No pathogenic bacteria were found in ants from the laboratory installation.